Debt reduction and automatic stabilisation - Paul Hiebert; Javier J. Pérez; Massimo Rostagno (European Central Bank (ECB), 2002)
This paper presents an optimal fiscal policy response to address the basic trade-off between the automatic stabilisation properties of budgets and the long run fiscal positions. The framework is an overlapping generations model la Weil (1989), extended to account for stochastic endowments and borrowing constrained households. A benign government chooses over the optimal degree of responsiveness of net taxes to individual incomes, an optimal measure of long-run public debt, or both, in order to smooth households' consumption across states of nature. In the presence of a deficit constraint for the government, the results unambiguously point to the desire for lower debt levels than those currently prevailing in order to enable a more effective hedging of personal income uncertainty by means of more active fiscal stabilisers. Citizens in economies exhibiting more pronounced cycles will favour less automatic stabilisation combined with a more aggressive policy of debt reduction.
Keywords: H31; H63; E63; 330; Automatic stabilisation; Borrowing constraints; Consumption; public debt